2003
DOI: 10.1034/j.1600-0544.2003.02276.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived long‐term prognosis of teeth with orthodontically resorbed roots

Abstract: General practitioners were the most concerned about root resorption. Although most practitioners feel 50% root resorption is significant and detrimental to the longevity of the tooth, extraction followed by prosthetic replacement was not an option. No agreement among practitioners when orthodontic treatment should be terminated; the general practitioners were conservative suggesting termination after 35% root loss. History of trauma, genetic disposition and root morphology are the most cited predisposing facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 13 publications
0
11
0
2
Order By: Relevance
“…Many general dentists and other dental specialists believe that EARR is avoidable and hold the orthodontist responsible when it occurs during orthodontic treatment (18). Histological studies reported greater than a 90% occurrence of EARR in orthodontically treated teeth (19).…”
Section: Discussionmentioning
confidence: 99%
“…Many general dentists and other dental specialists believe that EARR is avoidable and hold the orthodontist responsible when it occurs during orthodontic treatment (18). Histological studies reported greater than a 90% occurrence of EARR in orthodontically treated teeth (19).…”
Section: Discussionmentioning
confidence: 99%
“…6 Progressive OITRR can lead to a compromised crown to root ratio and compromised function. 7 Research has shown that OITRR can occur within 35 days. 8 With forces as light as 50 g, progressive apical resorption was accompanied with areas of cellular cementum repair.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of severe EARR during orthodontic treatment is reported to be 5%-18%, 7 and progressive EARR can lead to a compromised crown-to-root ratio and compromised tooth functioning. 8 However, the causes and mechanisms underlying EARR remain poorly characterized; this increases the risk associated with some orthodontic treatments.…”
Section: Introductionmentioning
confidence: 99%